Comparing the Utilizations of Radiofrequency, Bipolar Electrocauterization and Sutures for Bleeding Control in Circumcision (Annals of Medical Research, 2021)
Aim: The aim of this study was comparing the radiofrequency energy, bipolar-cautery and suture methods which were used for bleeding control in circumcision operations.
Keywords: s: Circumcision; Cauterization; Radiofrequency.